Case Report: First Case of Cefotaxime-Sulbactam-Induced Acute Intravascular Hemolysis in a Newborn With ABO Blood Type Incompatibility by the Mechanism of Non-Immunologic Protein Adsorption - Wu, Yuanjun; Wu, Yong; Yang, Yong; Chen, Baochan; Li, Jianqun; Guo, Ganping; Xiong, Fu (Frontiers in Immunology, 2021)
Background ABO blood type incompatibility hemolytic disease of newborn (ABO-HDN) and drug-induced immune hemolytic anemia (DIIHA) due to non-immunologic protein adsorption (NIPA) mainly cause extravascular hemolysis. All the reported severe DIIHA were caused by drug-induced antibodies, and rare report of acute intravascular hemolysis was caused by the NIPA mechanism or ABO-HDN. Case presentation We report the first case of acute intravascular hemolysis induced by cefotaxime sodium - sulbactam sodium (CTX - SBT) in a case of ABO-HDN which resulted in death at 55 h after birth. The mother’s blood type was O and RhD-positive, and the newborn’s blood type was B and RhD-positive. No irregular red blood cell (RBC) antibodies or drug-dependent antibodies related to CTX or SBT was detected in the mother’s plasma and the plasma or the RBC acid eluent of the newborn. Before the newborn received CTX - SBT treatment, the result of direct antiglobulin test (DAT) was negative while anti-B was positive (2 +) in both plasma and acid eluent. After the newborn received CTX - SBT treatment, the results of DAT for anti-IgG and anti-C3d were both positive, while anti-B was not detected in plasma, but stronger anti-B (3 +) was detected in acid eluent. In vitro experiments confirmed that NIPA of SBT promoted the specific binding of maternal-derived IgG anti-B to B antigen on RBCs of the newborn, thereby inducing acute intravascular hemolysis. Conclusion The NIPA effect of SBT promoted the specific binding of mother-derived IgG anti-B in newborn’s plasma to the newborn’s RBC B antigens and formed an immune complex, and then activated complement, which led to acute intravascular hemolysis. Drugs such as SBT with NIPA effect should not be used for newborns with HDN.